IMPLEMENTING DEMONSTRATION METHOD TO IMPROVE TEACHERS'PEDAGOGIC COMPETENCE DURING THE COVID-19 PANDEMICAT SLB MELATI RUMBAI - Maidar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
Based on the observations, some irregularities were found in the teacher's ability to teach. This was observed from the symptoms, such as some teachers were not able to develop a learning syllabus; they only used the old syllabus. Some teachers were not able to manage the class properly; some of them were not able to interact and communicate well with students; some others were not able to allocate the time properly and some teachers did not motivate the students to be actively involved in the learning process. This study aimed to determine the improvement of teachers’ pedagogical competence through demonstration method at SLBMelati Rumbai Pekanbaru. Based on the background description, the problem identification and problem limitation, the focus of this research was the Implementation of Demonstration Method in Improving Teachers’ Pedagogic Competence during the Covid-19 Pandemic at SLB Melati Rumbai Pekanbaru. This School Action Research was carried out only at SLB Melati Rumbai Pekanbaru. This research was conducted in two cycles. The duration of this research wa approximately 1 month. From the description of data processing and discussion, it was concluded that the teachers’ pedagogic competence in Cycle I was 65% with good category and it increased in Cycle II to 87% with very good category.